Influenced Encryption Key for AES based MF-TDMA in Mobile Communication - Ho Jeong, Won; Ju, Sang-Lim; Cho, Ju-Phil; Kim, Kyung-Seok (International Journal of Engineering and Technology, 2018)
In recent years, network security has become an important issue. Cryptography has been used for secure data and control access. In this paper, we analyze the effect of the key error according to plaintext size in the encrypted mobile communication. We have applied the Multi-Frequency Time-Division Multiple Access (MF-TDMA) based mobile communication environment and used the Advanced Encryption Standard (AES) algorithm. Simulator configured with the Convolutional Turbo Code (CTC) channel coder and Offset Quadrature Phase Shift Keying (OQPSK) modulation scheme and Additive White Gaussian Noise (AWGN) mobile channel. Depending on the length of the plaintext, we confirmed through the correlation of the bit error rate (BER) and the peak signal-to-noise ratio (PSNR). In addition, we analyze the correlation according to SNR in AES Counter (CTR) and Cipher-Block Chaining (CBC) mode and analyze the effect of encryption algorithm on communication. Finally, this study is used as data to analyze the performance of application of cryptographic service and various communication environments in the environment of MF-TDMA based mobile communication, and it is expected that it will be useful for performance analysis of image data restoration.Â